2020
DOI: 10.1002/anie.202010309
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Strong Chalcogen Bonds Involving Chalcogen‐Containing Heterocycles

Abstract: Chalcogen bonds are σ hole interactions and have been used in recent years as an alternative to hydrogen bonds. In general, the electrostatic potential at the chalcogen atom and orbital delocalization effects are made responsible for the orientation of the chalcogen bond. Here, we were able to show by means of SAPT calculations that neither the induction (orbital delocalization effects) nor the electrostatic term is causing the spatial orientation of strong chalcogen bonds in tellurium‐containing aromatics. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 61 publications
2
71
0
2
Order By: Relevance
“…We believe the systematic evidence and specific findings described herein not only provides new mechanistic guidance in understanding haloaddition and halocyclization reactions of alkenes and alkynes, especially those catalyzed by quinuclidine‐bearing cinchona alkaloids as illustrated by the groups of Yeung , Tang , Henneke , Denmark , Ishihara , Yamamoto and others, [33–42,61–78] but also provides fundamental knowledge in expanding halogen bond‐based reactions in synthesis, particularly concerning iodine‐based reagents and amine catalysis. Wider implications of the current work to chalcogen‐ and pnictogen‐based Lewis acids, which similarly feature sigma‐hole acceptor capabilities, is an intriguing proposition and represents a growing field of applications in catalysis, anion‐transport and may even be considered a less ‘unorthodox’ approach to the design of new reactions and methods in the future [79–84] …”
Section: Discussionmentioning
confidence: 99%
“…We believe the systematic evidence and specific findings described herein not only provides new mechanistic guidance in understanding haloaddition and halocyclization reactions of alkenes and alkynes, especially those catalyzed by quinuclidine‐bearing cinchona alkaloids as illustrated by the groups of Yeung , Tang , Henneke , Denmark , Ishihara , Yamamoto and others, [33–42,61–78] but also provides fundamental knowledge in expanding halogen bond‐based reactions in synthesis, particularly concerning iodine‐based reagents and amine catalysis. Wider implications of the current work to chalcogen‐ and pnictogen‐based Lewis acids, which similarly feature sigma‐hole acceptor capabilities, is an intriguing proposition and represents a growing field of applications in catalysis, anion‐transport and may even be considered a less ‘unorthodox’ approach to the design of new reactions and methods in the future [79–84] …”
Section: Discussionmentioning
confidence: 99%
“…Although a correlation between the experimentally observed conformational free energy differences and the energies of the orbitals containing n→σ* delocalization was observed, we caution that such correlations do not necessarily demonstrate causality, especially when considered alongside recent SAPT examinations suggesting that orbital interactions are not always dominant in chalcogen bonds. 61 Chalcogen bonding interactions have been implicated in the mechanism of isochalcogenureacatalyzed kinetic resolutions of secondary benzylic alcohols. 62 These reactions proceed via an acylated intermediate containing a carbonyl-chalcogen contact (Figure 10C).…”
Section: Metallophilic Interactionsmentioning
confidence: 99%
“…16,17 Of particular attention is a specific cyclic interaction motif containing two conventional Ch⋯N contacts, so-called 2Ch-2N squares, was currently investigated as a supramolecular synthon in crystal engineering and materials science. 18,19 Such square ChBs were also characterized as electrostatic interactions with significant orbital and dispersion contributions, [20][21][22] and the introduction of some strong electron-withdrawing substituents can strengthen these interactions. 12 However, to the best of our knowledge, very few studies on square ChB interactions involving hypervalent chalcogens have been reported so far.…”
Section: Introductionmentioning
confidence: 99%